Effect of risk enhancers versus technical aspects of high thrombotic risk criteria on adverse clinical events after PCI: insights from 2020 ESC NSTE-ACS Guidelines. (14th October 2021) - Wang, H Y; Xu, B; Zhang, R; Guan, C D; Dou, K F
Abstract: Background: The long-term clinical outcome after PCI is affected by various clinical and angiographic risk features. The present study was designed to investigate the long-term prognostic impact of risk enhancers and technical aspects as defined by 2020 ESC NSTE-ACS Guidelines for high thrombotic risk (HTR) criteria on the risk of adverse events after PCI. Methods: A total of 10, 167 patients were enrolled from the Fuwai PCI registry. Risk enhancers and technical aspects were retrospectively assessed according to 2020 ESC NSTE-ACS Guidelines. Risk enhancers were defined as having at least one of the following characteristics: diabetes mellitus requiring medication, history of recurrent MI, any multivessel CAD, peripheral artery disease, premature (<45 years) CAD, and chronic kidney disease. Technical aspects were defined as having at least one of the following characteristics: ≥3 stents implanted, ≥3 lesions treated, total stent length >60 mm, left main PCI, bifurcation stenting with ≥2 stents implanted, and chronic total occlusion. The primary endpoint was 30-month major adverse cardiac and cerebrovascular events (MACCE, a composite of cardiac death, myocardial infarction [MI], stent thrombosis, any revascularization, and ischemic stroke). Results: MACCE occurred in 1188 (11.7%) patients during the follow-up period (median duration: 881 days). Risk enhancers were present in 8, 437 patients (83.0%) and was associated with increased 30-month risk for the MACCE (adjusted hazard ratio [adjHR]: 2.11; 95% CI: 1.72–2.60). Technical aspects were present in 3, 335 patients (32.8%) and was an independent predictor of MACCE at 30 months (adjHR: 1.32; 95% CI: 1.17–1.49). The risk of MACCE associated with risk enhancers was significantly higher than for technical aspects (2.11 vs. 1.32; relative risk [RR]: 1.60; 95% CI: 1.47–1.75). Results were consistent when risk enhancers and technical aspects were modeled as a continuous variable. Adjusted HRs of MACCE within the 12 months for patients with risk enhancers and technical aspects were 2.35 (95% CI: 1.80–3.07) and 1.50 (95% CI: 1.30–1.73), respectively. Risk enhancers significantly influenced MACCE beyond 12 months (adjHR: 1.78; 95% CI: 1.29–2.46), whereas technical aspects were not associated with very late (12-month to 30-month) MACCE (adjHR: 1.01; 95% CI: 0.82–1.25). Both risk enhancers and technical aspects were not significantly associated with BARC type 2, 3, or 5 bleeding within 12 months and between 12 and 30 months. Conclusions: Both risk enhancers and technical aspects of HTR criteria significantly affected long-term ischemic clinical events but not major bleeding in patients undergoing PCI. Risk enhancers appeared to have a greater and more prolonged effect on poor prognosis than technical aspects, suggesting the importance of compliance with guideline-directed medical therapy. Funding Acknowledgement: Type of funding sources: Foundation. Main funding source(s): Beijing Municipal Health Commission (Grant No. 2020-1-4032)Chinese College of Cardiovascular Physicians, CS Optimizing Antithrombotic Research Fund (Grant number: BJUHFCSOARF201801-01)